The Rise and Fall Ali Baba Company Has Encountered Throughout Their Success - Pusparajan A/L Antony Das; Daisy Mui Hung Kee; Geethanapriya A/P Sathiyananthan; Nur Amirah; Linarani A/P Muniandy; Anfal Alrashidi; Majdi Anwar Quttainah; Asla Alosaimi; Deepali Verma; Rudresh Pandey (AIBPM Publisher, 2020)
Having a company, it comes with the opportunities to prosper or the risk of falling. Any company needs to go through this moment for it to keep on growing. The purpose of this paper is to examine the rise and fall of Alibaba throughout its success. The study used mostly known factors from other research results on Alibaba Company and analyze those factors effect on ups and downs of Alibaba. Some of the factors including Jack Ma's relation with investors and customers, business model, integrated ecosystem, and such. This study improves the understanding of circumstances that a company will have to go through which can be utilized by top management to strategize their plan.